A Baseline Measurement of Quality of Life in 322 Adults With Osteogenesis Imperfecta. (7th November 2020) - Gooijer, Koert; Harsevoort, Arjan G J; van Dijk, Fleur S; Withaar, Hendrikje (Rik); Janus, Guus J M; Franken, Anton A M
ABSTRACT: Osteogenesis imperfecta (OI) is characterized by bone fragility and secondary features such as blue sclerae, dentinogenesis imperfecta, hearing loss, ligamentous laxity, and short stature. It was thought that health‐related quality of life (QoL) in patients with OI mainly depends on the severity of the skeletal deformities. However, it has become clear that additional factors can affect the QoL in all patients with OI. In this study, we compare dimensions of QoL in adults with OI with a control population. The SF‐36 questionnaire was distributed among 330 adult patients with different OI types. Results were compared with two control populations from the Netherlands. Age‐matched comparisons were made with one of the two control populations. The results were summarized in eight domains: general and mental health, physical and social function, bodily pain, vitality, and physical and emotional role. General health and physical function in all types of OI are low compared with controls, except patients with OI type 4 aged 55+ years. Bodily pain in patients with OI appeared significantly worse than in the control population. There was no significant difference between OI types regarding pain and vitality. Vitality was only in the OI type 1 group significantly lower compared with controls. Patients with OI type 1 had a significantly reduced mental health. Social functioning appeared most effective in type 3 around 20 years of age. QoL in adult patients with OI should be an important outcome measure in every OI clinic, but the amount of baseline data on this subject is sparse. This baseline measurement study is the largest study to date investigating QoL in adult patients with OI. The mean scores indicate that people with OI generally have a significantly lower QoL than the control population. Further qualitative evaluation of QoL and its influences is important for future management. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.